Central bank losses and commercial bank profits: Unexpected and unfair? - Thomas Jost; Reimund Mink (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2024)
The Eurosystem and the Deutsche Bundesbank will incur substantial losses in 2023 that are likely to persist for several years. Due to the massive purchases of securities in the last 10 years, especially of government bonds, the banks' excess reserves have risen sharply. The resulting high interest payments to the banks since the turnaround in monetary policy, with little income for the large-scale securities holdings, led to massive criticism. The banks were said to be making "unfair" profits as a result, while the fiscal authorities had to forego the previously customary transfers of central bank profits. Populist demands to limit bank profits by, for example, drastically increasing the minimum reserve ratios in the Eurosystem to reduce excess reserves are creating new severe problems and are neither justified nor helpful. Ultimately, the EU member states have benefited for a very long time from historically low interest rates because of the Eurosystem's extraordinary loose monetary policy and must now bear the flip side consequences of the massive expansion of central bank balance sheets during the necessary period of monetary policy normalisation. – – Das Eurosystem und die Deutsche Bundesbank werden im Jahr 2023 und wahrscheinlich auch in den kommenden Jahren beträchtliche Verluste einfahren. Durch die massiven Wertpapierkäufe der letzten zehn Jahre, insbesondere von Staatsanleihen, sind die Überschussreserven der Banken stark gestiegen. Die daraus resultierenden hohen Zinszahlungen an die Banken seit der Wende in der Geldpolitik, bei zugleich geringer Verzinsung der hohen Wertpapierbestände, führten zu massiver Kritik. Die Banken machten dadurch "unfaire" Gewinne, während der Fiskus auf die bisher üblichen Abführungen von Zentralbankgewinnen verzichten musste. Populistische Forderungen, die Gewinne der Banken zu begrenzen, indem z.B. die Mindestreservesätze im Eurosystem drastisch erhöht werden, um die Überschussreserven zu reduzieren, schaffen neue Probleme und sind weder sachlich gerechtfertigt noch hilfreich. Schließlich haben die EWU-Staaten aufgrund der ultra-expansiven Geldpolitik des Eurosystems sehr lange in beispielloser Weise von historisch niedrigen Zinsen profitiert und müssen nun die fiskalischen Folgen der massiven Ausweitung der Zentralbankbilanzen in der Phase der notwendigen geldpolitischen Normalisierung tragen.
Keywords: E50; E58; 330; Central Bank Losses; Eurosystem; Quantitative Easing; Minimum Reserves; Monetary Policy